Effect of Antimony Trioxide and Carbon Black on the Mechanical Properties and Ablation Properties of Liner Insulation in Rocket Motors - Thirapat Kitinirunkul; Prakob Kitchaiya; Chesda Kiriratnikom; Paisarn Boonyarat; Suchuchchai Nuanklai (Key engineering materials, 2021)
This study focused on the mechanical properties and ablation properties of liner insulation in rocket motors for improving rocket performance by means of tensile strength, elongation, ablation rate and density. The following parameters were varied: amount of zinc oxide, antimony trioxide and carbon black (N550). It was found that the insulation of the rocket motors with antimony trioxide and carbon black provided higher the elongation and ablation rate. Thus, it was able to endure more heat from hot gas in combustion chamber. The result suggests that use of antimony trioxide and carbon black as filler in liner insulation can improve the thermal insulators and case-bonded in rocket motor between the solid propellant and the rocket motor tube.
Keywords: Rocket and propulsion systems research; Energetic Materials and Combustion; Gas Dynamics and Kinetic Theory